Penerapan Teknologi Perbaikan Fungsi Reproduksi Sapi Pedaging pada Kelompok Masyarakat BUMDes Peternakan di Desa Teluk Kampe, Kepulauan Selayar: Implementation of Technology to Improve the Reproductive Function of Beef Cattle in the BUMDes Livestock Community Group in Teluk Kampe Village, Selayar Islands - Hasrin, Hasrin; Zulkharnaim, Zulkharnaim; Hasman, Hasman; Syamsuddin, Syamsuddin; Wulandari, Sri Helda; Sari, Anggun Permata; Nurhidayah, Asmaul Fitriana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Recording of livestock reproduction is necessary for farmers to improve reproductive aspects of their animals. A common issue faced by beef cattle farmers is their limited knowledge; they often rely on experience without a solid foundation of technical knowledge. The goal of the program is to enhance the knowledge of smallholder farmers about reproductive management, thereby increasing the productivity of beef cattle. The target audience for this activity is the members of the farming community in Teluk Kampe Village. The methods used in this service program include extension and training on reproductive management and the application of recording. The outcomes of this service activity are reflected in the increased knowledge of farmers in Teluk Kampe Village and their motivation to improve the reproductive management of their beef cattle, based on the analysis of pre-test and post-test results. The application of reproductive function improvement technologies for beef cattle is expected to help boost productivity and improve the economic situation of smallholder farmers if implemented properly.